Tropical cyclone enhanced vertical transport in the northwestern South China Sea I: Mooring observation analysis for Washi (2005). (5th April 2020) - Wang, Liju; Xie, Lingling; Zheng, Quanan; Li, Junyi; Li, Mingming; Hou, Yijun
Abstract: Using mooring-observed horizontal velocities and temperature from July 28 to August 2, 2005, this study analyzes the temporal-vertical variation of the diagnostic vertical velocity and mass transport during passage of tropical storm Washi (2005) over the northwestern continental shelf of the South China Sea (SCS). The results show that the total vertical velocity is of the order of O (1 × 10 −4 ) m s −1 in the mixed layer above 25 m, and of O (1 × 10 −5 ) m s −1 in the lower layer. Dynamically, the geostrophic advection and unsteady behavior of density induced by near-inertial oscillation are dominant factors in the upper and lower layers, respectively. As tropical storm Washi (2005) passed by from July 29 to 31, 2005, the upward vertical velocity was dominant and significantly enhanced to the order of O (1 × 10 −3 ) m s −1 . The diagnosed vertical velocity in the upper layer is one order greater than the averaged Ekman pumping velocity, which occurred one day earlier. The vertical advection transport calculated from the diagnosed vertical velocity reaches O (1 × 10 −5 ) kg s −1 m −3, one order greater than that induced by turbulent mixing. Time-averaged transports by vertical advection and mixing are both upward in the layer above the thermocline during the storm passage. Highlights: Storm-induced vertical velocity and transport are diagnosed from mooring observations. Geostrophic and unsteady components dominate variation of the vertical velocity. Upward velocity was enhanced to O (1 × 10 −3 ) m s −1 as storm Washi (2005) passed. Diagnosed vertical velocity is one order larger and one day later than Ekman pumping. Vertical advection transport of O (1 × 10 −5 ) kg s −1 m −3 is greater than mixing diffusion flux.